Implementasi Media Papan Rahasia Dalam Meningkatkan Kemampuan Komunikasi dan Kolaborasi Siswa Kelas VI di MI Roudlatul Khuffadz - salmawati adam; Sella Nofriska Sudrimo (MISOOL: Jurnal Pendidikan Dasar, 2025)
This article aims to evaluate the implementation of The Secret Board media in improving communication and collaboration skills using the jigsaw model learning method in Class VI students in Mathematics at MI Roudlatul Khuffadz. The student population amounted to 32 students in a Class VI with a sample taken amounted to 16 students from that class. This study uses a qualitative approach with descriptive data collected through observation, interviews, and document analysis. The results showed that the secret board Learning media can create an interactive learning environment, increase student participation, confidence in communication, and good teamwork skills, as well as increase learning motivation. This study concludes that this media is effective and can be used as a reference for teachers to design learning strategies that are more interactive and collaborative